Impact of Eracs on Post-Caesarean Pain: A Study at Pelni Hospital, Jakarta - Tantri Wenny Sitanggang; Mira Suminar; Irma Rahmania (Viva Medika, 2025)
Background: Data from the WHO Global Survey On Maternal And Perinatal Health shows that 46.1% of all births are performed by SC method. The WHO states that the incidence of chronic pain after SC delivery is as high as 18% and more than 80% of patients undergoing post-cesarean recovery experience pain, with approximately 75% of these patients describing moderate, severe or very severe pain. Enhanced recovery care methods are an effective way to do this. This can lead to an earlier rehabilitation and discharge process and in SC patients is known as Enhanced Recovery After Caesarian Surgery (ERACS). Research Objective: To determine the relationship between ERACS method and pain level after sectio caesarian (SC) at Pelni Hospital Jakarta in 2024. Research Methodology: Quantitative research with case control research design. The study population was all post partum mothers with SC at Pelni Hospital Jakarta in January 2024, which was 148 people and the sample obtained was 66 people. Bivariate analysis was performed with chi square test. Research Results: Univariate analysis found that most of the age is not at risk (age 20 - 35 years) as many as 54 people (81.82%), most of them have high school education, namely 40 people (60.61%), most of the mothers work, namely 36 people (55.54%). Bivariate analysis found that there is a relationship between the ERACS method and the level of pain after Sectio Caesaria (SC) at Pelni Hospital Jakarta p value (0.000) and with an OR value: 1.435 which means there is a 1.435 times chance of experiencing pain in Non Eracs labour compared to the ERACS method. Conclusion: There is a relationship between ERACS method and pain level after Sectio Caesaria (SC) at Pelni Hospital Jakarta. Suggestion: For hospitals to be able to help facilitate and prepare the necessary media for each room in organising activities.